Bipolar membrane based on charged nanosheet catalyst layer, preparation method of bipolar membrane and application of bipolar membrane in seawater dissociation
By introducing modified charged nanosheets into the intermediate layer of the bipolar membrane to form a charged channel, the problems of high hydrolysis voltage and ion leakage of traditional bipolar membranes are solved, and the effects of efficient catalytic hydrolysis and low homo-ion leakage are achieved.
Patent Information
- Application Number
- CN202411814900.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional bipolar membranes require a high transmembrane voltage during hydrodissociation, and the unsatisfactory membrane layer causes ions to pass through migration and diffusion, affecting the current efficiency.
Using a bipolar membrane preparation method based on the catalytic layer of charged nanosheets, a sub-nanometer or nano-level charged channel is formed in the intermediate layer of the bipolar membrane by ultrasonic spraying, and the nanosheet spacing is regulated to achieve efficient catalytic hydrolysis and limit the leakage of homo ions.
Low isoion leakage and excellent hydrodissociation performance are achieved, the hydrodissociation voltage is reduced to 0.77V, and the first limit current density is as low as 1.5mA cm-2, improving the current efficiency.
Smart Images

Figure HDA0005182203750000011 
Figure HDA0005182203750000012 
Figure HDA0005182203750000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material technology, and in particular relates to a bipolar membrane based on a charged nanosheet catalytic layer, a preparation method thereof, and an application thereof in seawater dissociation. Background Art
[0002] Bipolar membrane (BPM) is composed of a polymer cation exchange layer (CEL) that selectively conducts cations, an anion exchange layer (AEL) that selectively conducts anions, and an intermediate catalyst layer. When a reverse voltage is applied, that is, the polymer cation exchange layer faces the cathode and the polymer anion exchange layer faces the anode, water in the intermediate catalyst layer dissociates into H + and OH - , and diffuse to both sides of the membrane layer, realizing the conversion of electrical energy into chemical energy in the form of proton chemical potential difference (i.e. pH gradient). The ideal bipolar membrane can prevent ions on both sides of the membrane from crossing the entire membrane layer, so that the two sides of the membrane are in different environments. Therefore, BPM is used in energy conversion, resource recovery and food processing today.
[0003] The membrane layer is not ideal. The ions on both sides of the membrane are mainly transferred to the other side through the uncharged inter-cluster space through migration and diffusion, resulting in low current efficiency in practical applications. In addition, in traditional bipolar membranes, water is dissociated into H + and OH - The transmembrane voltage required for the process is relatively high. Introducing excellent water dissociation catalysts to regulate the bipolar membrane intermediate layer can effectively reduce the transmembrane voltage. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a bipolar membrane based on a charged nanosheet catalytic layer and a method for preparing the same. The intermediate layer in the bipolar membrane prepared by this method utilizes sub-nanometer or nanometer-level charged channels formed by stacking nanosheets, which, under the action of an electric field, achieves efficient catalytic water dissociation while limiting the leakage of common ions.
[0005] The present invention provides a method for preparing a bipolar membrane based on a charged nanosheet catalyst layer, comprising the following steps:
[0006] A) applying a cation (anion) exchange membrane liquid on a smooth substrate and drying it to obtain a cation (anion) exchange membrane layer;
[0007] dissolving the modified charged nanosheets to obtain a modified charged nanosheet solution;
[0008] B) ultrasonically spraying the modified charged nanosheet solution on the cation (anion) exchange membrane layer, and drying to obtain a bipolar membrane intermediate layer;
[0009] C) spraying anion (cation) exchange membrane liquid onto the bipolar membrane middle layer, and drying to obtain a bipolar membrane.
[0010] Preferably, the surface modification groups of the modified charged nanosheets are one or more of ions, ionic groups, colloidal molecules and polymer molecules with a size of 0.1 to 20 nm;
[0011] The modified charged nanosheets are boron nitride nanosheets, MXene nanosheets, graphene family nanosheets, hydrotalcite nanosheets, disulfide nanosheets, zeolite nanosheets, MOF nanosheets or TiO2 nanosheets.
[0012] Preferably, the mass concentration of the cation (anion) exchange membrane liquid is 1 to 10%;
[0013] The solvent in the cation (anion) exchange membrane liquid is one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide.
[0014] Preferably, the drying temperature in step A) is 50-90°C, the drying time is 1-48h; the thickness of the cation (anion) exchange membrane layer is 1-40 μm;
[0015] The drying temperature in step C) is 50-90° C. and the drying time is 1-48 hours; the thickness of the anion (cation) exchange membrane layer is 1-40 μm.
[0016] Preferably, the solvent used to dissolve the modified charged nanosheets is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide;
[0017] The mass volume ratio of the modified charged nanosheets and the solvent is (0.1-1) g: (200-1000) mL.
[0018] Preferably, the thickness of the bipolar membrane intermediate layer in step B) is 4 to 400 nm;
[0019] The loading amount of the modified charged nanosheets on the cation (anion) exchange membrane layer is 1 to 1000 μg / cm -2 .
[0020] Preferably, the drying temperature in step B) is 50-90°C.
[0021] Preferably, the mass concentration of the anion (cation) exchange membrane liquid in step C) is 1 to 10%;
[0022] The solvent in the anion (cation) exchange membrane liquid is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide.
[0023] Preferably, the height of spraying in step B) and step C) is 1 to 10 cm;
[0024] The solution spray rate was set at 0.05-0.8 mL min -1 , feed speed is 5~40mm·s -1 .
[0025] The present invention provides a bipolar membrane based on a charged nanosheet catalyst layer, which is prepared by the preparation method described in the above technical solution.
[0026] The present invention provides a method for preparing a bipolar membrane based on a charged nanosheet catalyst layer, comprising the following steps: A) coating a cation (anion) exchange membrane liquid on a smooth substrate, drying to obtain a cation (anion) exchange membrane layer; dissolving a modified charged nanosheet to obtain a modified charged nanosheet solution; B) ultrasonically spraying the modified charged nanosheet solution on the cation (anion) exchange membrane layer, drying to obtain a bipolar membrane intermediate layer; C) ultrasonically spraying an anion (cation) exchange membrane liquid onto the bipolar membrane intermediate layer, drying to obtain a bipolar membrane. The present invention adopts the idea of introducing confined mass transfer into the bipolar membrane intermediate layer, stacks positively (negatively) charged nanosheets by ultrasonic spraying, and constructs a bipolar membrane intermediate layer by modifying the positively (negatively) charged nanosheets to adjust the spacing, thereby preparing a bipolar membrane with low common ion leakage and excellent water dissociation performance. The sub-nanometer or nanometer-level charged channels formed by stacking the modified charged nanosheets in the bipolar membrane intermediate layer will limit common ion leakage. The experimental results show that the intermediate layer bipolar membrane can be constructed by regulating the distance between charged nanosheets at 100 mA cm -2 The water dissociation voltage is only 0.77 V and the first limiting current density is as low as 1.5 mA cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the process of preparing a bipolar membrane based on a charged nanosheet catalyst layer according to the present invention;
[0028] Figure 2 This is a scanning electron microscope morphology image of a cross section of a bipolar membrane based on a charged nanosheet catalyst layer prepared in Example 1 of the present invention at 1000 times magnification;
[0029] Figure 3 This is a scanning electron microscope morphology image at a high magnification (10,000 times) of a cross section of a bipolar membrane based on a charged nanosheet catalyst layer prepared in Example 1 of the present invention;
[0030] Figure 4 This is a current-voltage curve of a bipolar membrane based on a charged nanosheet catalyst layer prepared in Example 1 of the present invention;
[0031] Figure 5 The first limiting current density diagram of the bipolar membrane based on the charged nanosheet catalyst layer prepared in Example 1 of the present invention;
[0032] Figure 6 This is a diagram of the first limiting current density of a bipolar membrane based on a charged nanosheet catalyst layer prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a bipolar membrane based on a charged nanosheet catalyst layer, comprising the following steps:
[0034] A) applying a cation (anion) exchange membrane liquid on a smooth substrate and drying it to obtain a cation (anion) exchange membrane layer;
[0035] dissolving the modified charged nanosheets to obtain a modified charged nanosheet solution;
[0036] B) ultrasonically spraying the modified charged nanosheet solution on the cation (anion) exchange membrane layer, and drying to obtain a bipolar membrane intermediate layer;
[0037] C) ultrasonically spraying anion (cation) exchange membrane liquid onto the middle layer of the bipolar membrane, and drying to obtain a bipolar membrane.
[0038] The method provided by the present invention introduces the idea of confined mass transfer in the middle catalytic layer, stacks the modified charged nanosheets by ultrasonic spraying, and constructs the bipolar membrane middle layer by regulating the spacing of the modified charged nanosheets, thereby preparing a bipolar membrane with low common ion leakage and excellent water dissociation performance. The sub-nanometer or nanometer-level charged channels formed by the stacking of the modified charged nanosheets in the middle layer of the bipolar membrane will limit the leakage of common ions.
[0039] The present invention applies a cation (anion) exchange membrane liquid on a smooth substrate and dries it to obtain a cation (anion) exchange membrane layer. The cation (anion) exchange membrane liquid in the present invention is prepared by uniformly mixing sulfonic acid type polyphenylsulfone powder particles with an organic solvent; the mass concentration of the cation (anion) exchange membrane liquid is 1 to 10%; the solvent in the cation (anion) exchange membrane liquid is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide. The heating temperature used in the drying is 50 to 90°C, preferably 55 to 70°C; the time is 1 to 48 hours, preferably 4 to 20 hours. The thickness of the cation (anion) exchange membrane layer is 1 to 40 μm.
[0040] Specifically, the cation exchange membrane liquid in the present invention is a sulfonic acid type polyphenylsulfone membrane liquid; the smooth substrate is a smooth glass plate; the heating temperature is 60° C., the heating time is 5 hours; and the thickness of the cation (anion) exchange membrane layer is 6.5 μm.
[0041] The present invention dissolves the modified charged nanosheet to obtain a modified charged nanosheet solution. The present invention modifies the surface of the charged nanosheet by electrostatic attraction and chemical modification; the surface modification group of the modified charged nanosheet is selected from one or more of ions, ionic groups, colloidal molecules and polymer molecules with a size of 0.1 to 20 nm; the modified charged nanosheet is a boron nitride nanosheet, a MXene nanosheet (negatively charged), a graphene family nanosheet, a hydrotalcite nanosheet (positively charged), a disulfide nanosheet, a zeolite nanosheet (negatively charged), a MOF nanosheet or a TiO2 nanosheet. Boron nitride nanosheets, disulfide nanosheets, MOF nanosheets or TiO2 nanosheets are not charged themselves, but can be charged by modification; or the nanosheets of the above types that are originally uncharged are modified to be charged. Graphene nanosheets are not charged themselves, but their surface can be changed to change their charge state by chemical modification or material treatment, such as graphene oxide being negatively charged.
[0042] The invention ultrasonically sprays the modified charged nanosheet solution on the cation (anion) exchange membrane layer, and dries the solution to obtain a bipolar membrane intermediate layer.
[0043] It should be noted that if the charged nanosheets are modified or modified in a solution, they do not need to be dissolved in a solvent. The modified charged nanosheets in the present invention are nanosheets with positive (negative) charges.
[0044] The present invention can use ordinary (uncharged) nanosheets without modification or modification, and modify them to be charged nanosheets; the charged nanosheets can be further modified to increase the stacking distance of the nanosheets. If the charged nanosheets themselves are charged, they can be used directly without modification.
[0045] Specifically, the present invention dissolves negatively charged MXene nanosheets in water at a mass concentration of 0.25 mg ml -1 , add Fe(OH)3 colloidal solution and stir for 30 min to obtain the modified negatively charged MXene nanosheet solution.
[0046] The present invention ultrasonically sprays the modified charged nanosheet solution on the cation (anion) exchange membrane layer and then dries it at a temperature of 50 to 90°C for 1 to 48 hours; the thickness of the anion (cation) exchange membrane layer is 1 to 40 μm. The height of the ultrasonic spraying is 1 to 10 cm, and the solution spraying rate is set to 0.05 to 0.8 mL min -1 , feed speed is 5~40mm·s -1 .
[0047] The thickness of the bipolar membrane intermediate layer in the present invention is 4-400nm, and the loading amount of the modified charged nanosheet on the cation (anion) exchange membrane layer is 1-1000μg / cm -2The bipolar membrane middle layer is a bipolar membrane middle layer in which modified charged nanosheets are stacked layer by layer and the interlayer spacing is modified.
[0048] Specifically, the mass concentration was 0.25 mg ml -1 The negatively charged MXene nanosheet solution modified with Fe(OH)3 was ultrasonically sprayed onto the sulfonic acid polyphenylene ether cation exchange membrane layer. The spraying height was 5 cm and the solution spraying rate was 0.2 ml min -1 , feed speed is 25mm s -1 The heating temperature is 80°C, the height of the catalyst layer is about 20 nm, and the loading amount of positively (negatively) charged nanosheets is 12 μg / cm -2 , and drying to obtain the regulated spacing between charged nanosheets to construct the intermediate layer.
[0049] The invention ultrasonically sprays anion (cation) exchange membrane liquid onto the middle layer of the bipolar membrane, and dries the mixture to obtain the bipolar membrane.
[0050] In the present invention, the mass concentration of the anion (cation) exchange membrane liquid is 1 to 10%. The solvent in the anion (cation) exchange membrane liquid is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide. The height used for ultrasonic spraying of the anion (cation) exchange membrane liquid is 1 to 10 cm; the solution spraying speed is set to 0.05 to 0.8 mL·min -1 , feed speed is 5~40mm·s -1 The drying temperature is 50-90°C, the drying time is 1-48 hours, and the thickness of the anion (cation) exchange membrane layer is 1-40 μm.
[0051] The anion exchange membrane liquid in the present invention is a polyterphenyl aryl piperidone anion exchange membrane liquid; the present invention uses an ultrasonic spraying method to evenly spray the polyterphenyl aryl piperidone anion exchange membrane liquid on the intermediate layer, heats and dries it, and obtains a bipolar membrane constructed by regulating the distance between charged nanosheets.
[0052] Specifically, a glass sheet loaded with a cationic membrane layer and an intermediate layer was placed in a precision ultrasonic spraying instrument, the heating temperature was set to 80°C, and a polyterphenyl aryl piperidone anion exchange membrane liquid with a mass concentration of 3.2% was sprayed on the catalytic intermediate layer. The anion exchange membrane liquid solvent was dimethyl sulfoxide. The spraying height was 5 cm and the solution spraying rate was 0.2 ml min -1 , feed speed is 25 mm·s -1 The heating temperature was 80°C, and heating was continued for 5 hours after spraying to obtain a polyterphenyl aryl piperidone anion exchange membrane layer with a thickness of 32.5 μm, and a bipolar membrane based on a charged nanosheet catalyst layer was obtained.
[0053] See also Figure 1, a method for preparing a bipolar membrane based on a charged nanosheet catalyst layer comprises:
[0054] S100: coating the cation (anion) exchange membrane liquid on a smooth substrate and drying it to obtain a cation (anion) exchange membrane layer;
[0055] S200: modification of positively (negatively) charged nanosheets;
[0056] S300: ultrasonically spraying a modified positively (negatively) charged nanosheet solution on the cation (anion) exchange membrane layer, and drying to obtain a bipolar membrane intermediate layer with positively (negatively) charged nanosheets stacked layer by layer and with modified interlayer spacing;
[0057] S400: spraying anion (cation) exchange membrane liquid on the middle layer of the bipolar membrane, drying, and obtaining a bipolar membrane.
[0058] The present invention also provides an application of the bipolar membrane based on the charged nanosheet catalytic layer described in the above technical solution in seawater dissociation.
[0059] The present invention simulates the transmembrane potential difference of a bipolar membrane based on a charged nanosheet catalytic layer in a 0.5 mol / L NaCl solution.
[0060] In order to further illustrate the present invention, a bipolar membrane based on a charged nanosheet catalyst layer provided by the present invention, a preparation method thereof, and an application in seawater dissociation are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0061] The present invention provides a method for preparing a bipolar membrane based on a charged nanosheet catalyst layer. The technical solutions in the embodiments of the present invention will be described in detail and clearly in combination with the embodiments of the present invention. It should be particularly noted that the specific embodiments described herein are only part of the embodiments of the present invention, not all of them. All similar replacements and modifications are obvious to technicians in this field, and they all belong to the scope of protection of the present invention. All other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0062] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0063] An embodiment of the present invention provides an embodiment of a method for preparing an intermediate layer bipolar membrane by regulating the spacing between charged nanosheets. It should be noted that although the logical order is shown in the flow chart, in some cases, the steps shown or described may be performed in a different order than here.
[0064] Example 1
[0065] A 1.6% sulfonic acid polyphenylsulfone cation exchange membrane liquid is coated on a smooth glass plate, and the glass plate is heated and dried at 60° C. for 5 h to obtain a cation exchange membrane layer with a thickness of 6.5 μm.
[0066] Add Fe(OH)3 colloidal solution to 0.25mg ml -1 The negatively charged MXene aqueous solution was stirred for 30 min to obtain a Fe(OH)3-modified MXene nanosheet solution (MXene@Fe(OH)3); the Fe(OH)3-modified MXene nanosheet solution was sprayed on the cation exchange membrane by ultrasonic spraying at a spraying height of 5 cm and a solution spraying rate of 0.2 ml min -1 , feed speed is 25 mm·s -1 , the heating temperature is 80 °C, the height of the catalyst layer is about 20 nm, and the loading amount of (MXene@Fe(OH)3) is 12 μg / cm -2 , drying to obtain the regulated distance between charged nanosheets to construct the middle layer;
[0067] The glass sheet loaded with the cationic membrane layer and the intermediate layer is placed in a precision ultrasonic spraying instrument, the heating temperature is set to 80°C, and a polyterphenyl aryl piperidone anion exchange membrane liquid with a mass concentration of 3.2% is ultrasonically sprayed on the catalytic intermediate layer. The anion exchange membrane liquid solvent is dimethyl sulfoxide. The spraying height is 5 cm and the solution spraying speed is 0.2 ml min -1 , feed speed is 25mm s -1 The heating temperature was 80°C, and heating was continued for 5 hours after spraying to obtain a polyterphenyl aryl piperidone anion exchange membrane layer with a thickness of 32.5 μm, and a bipolar membrane based on a charged nanosheet catalyst layer was obtained.
[0068] The present invention performs a cross-sectional scanning electron microscope analysis on the bipolar membrane based on the charged nanosheet catalyst layer prepared in Example 1. The specific process is as follows:
[0069] A glass plate loaded with a bipolar membrane based on a charged nanosheet catalyst layer is placed in deionized water, and the bipolar membrane is automatically separated from the smooth glass plate. The bipolar membrane is taken out from the deionized water, dried using a hot plate and vacuum suction in a precision ultrasonic spraying device, and a portion of the bipolar membrane of appropriate size is cut and immersed in liquid nitrogen for a few seconds, and then taken out for low-temperature brittle fracture treatment. The prepared bipolar membrane cross-section sample is attached to the sample stage with conductive glue, and gold is sprayed on it. It is moved into the sample chamber of a scanning electron microscope for testing and observation, and a cross-sectional morphology of the bipolar membrane based on a charged nanosheet catalyst layer is obtained, as shown in FIG. Figure 2 The cross section was photographed at high magnification to observe the catalyst layer, as shown in Figure 3 shown.
[0070] Reference Figure 2 , Figure 2 The results show that the prepared bipolar membrane based on charged nanosheet catalyst layer has uniform membrane thickness, where the membrane thickness of the cation exchange membrane is 6.5 μm and the membrane thickness of the anion exchange membrane is 36.5 μm. There is a catalyst layer between the two membrane layers. Figure 3 It can be seen that the catalyst layer is evenly dispersed between the cation and cathode membrane layers, and the thickness of the catalyst layer is about 20nm.
[0071] The present invention also conducted a current-voltage curve test on the bipolar membrane prepared in Example 1, and the specific process is as follows:
[0072] First, the bipolar membrane based on the charged nanosheet catalyst layer to be tested in the present invention is immersed in 0.5 mol L -1 The bipolar membrane was then placed in a four-electrode device with two chambers for current-voltage testing. 0.5 mol L -1 Na2SO4 solution. Ag / AgCl electrode was used as the sensing electrode and reference electrode, and platinum electrode was used as the working electrode and counter electrode.
[0073] Under the action of the reverse direct current electric field, that is, the cation exchange membrane layer faces the negative electrode and the anion exchange membrane layer faces the positive electrode, the electrochemical workstation is used to measure the -1 Gradually increase the current and record the transmembrane potential difference. Plot the current and transmembrane voltage data to get the following result: Figure 3 The current-voltage curve of the bipolar membrane is shown.
[0074] like Figure 4 As shown in Figure 2, the voltage across the membrane increases with the current supplied. The bipolar membrane based on the charged nanosheet catalyst layer is -2 The water dissociation voltage is only 0.77V.
[0075] Similarly, under the action of a DC reverse electric field, an electrochemical workstation was used to measure the-1 The current was slowly increased while recording the bipolar membrane in simulated seawater, i.e., 0.5 mol L -1 The transmembrane potential difference in NaCl solution is used to plot the current and transmembrane voltage data in a current-voltage curve. The current corresponding to the maximum value of the derivative in the current-voltage curve is the first limiting current density.
[0076] See also Figure 5 The first limiting current density of the bipolar membrane based on the MXene@Fe(OH)3 charged nanosheet catalyst layer is 1.7 mA cm -2 , which shows that this type of bipolar membrane has extremely low common ion leakage, laying the foundation for maintaining the pH difference on both sides of the bipolar membrane and realizing the bipolar membrane in electrodialysis to produce acid and alkali, electrolysis of seawater to produce hydrogen, etc.
[0077] Example 2
[0078] The difference from Example 1 is that the middle layer is different, specifically:
[0079] The mass concentration is 0.25 mg mL -1 The negatively charged MXene nanosheet solution was ultrasonically sprayed onto the sulfonic acid polyphenylene ether cation exchange membrane layer, and the MXene loading was 12 μg cm -2 , 24 μg cm -2 、36μg cm -2 , and drying to obtain a regulated distance between charged nanosheets to construct an intermediate layer, and finally a bipolar membrane based on a MXene nanosheet catalytic layer is obtained.
[0080] Under the action of a reverse direct current electric field, an electrochemical workstation was used to generate a -1 Slowly increase the current while recording the bipolar membrane 0.5 mol L -1 The transmembrane potential difference in the Na2SO4 solution is plotted against the transmembrane voltage data in a current-voltage curve. The current corresponding to the maximum value of the derivative in the current-voltage curve is the first limiting current density.
[0081] See also Figure 6 , the MXene loading is 12 μg cm -2 , 24 μg cm -2 、36μg cm -2 The first limiting current density of the prepared bipolar membrane based on MXene charged nanosheet catalyst layer is 2.04 mA cm -2 , 1.70mA cm -2 and 1.36 mA cm -2, which shows that the common ion leakage of this type of bipolar membrane is extremely low. At the same time, the higher the MXene loading, that is, the thicker the catalyst layer, the lower the common ion leakage, which further illustrates the inhibitory effect of the catalyst layer on common ion leakage.
[0082] As can be seen from the above embodiments, the present invention provides a method for preparing a bipolar membrane based on a charged nanosheet catalyst layer, comprising the following steps: A) coating a cation (anion) exchange membrane liquid on a smooth substrate, drying to obtain a cation (anion) exchange membrane layer; dissolving a modified charged nanosheet to obtain a modified charged nanosheet solution; B) ultrasonically spraying the modified charged nanosheet solution on the cation (anion) exchange membrane layer, drying to obtain a bipolar membrane intermediate layer; C) ultrasonically spraying an anion (cation) exchange membrane liquid onto the bipolar membrane intermediate layer, drying to obtain a bipolar membrane. The present invention adopts the idea of introducing confined mass transfer into the bipolar membrane intermediate layer, stacks positively (negatively) charged nanosheets by ultrasonic spraying, and constructs a bipolar membrane intermediate layer by modifying the positively (negatively) charged nanosheets to adjust the spacing, thereby preparing a bipolar membrane with low common ion leakage and excellent water dissociation performance. The sub-nanometer or nanometer-level charged channels formed by the stacking of positively (negatively) charged nanosheets in the bipolar membrane intermediate layer will limit common ion leakage. The experimental results show that the intermediate layer bipolar membrane can be constructed by regulating the distance between charged nanosheets at 100 mA cm -2 The water dissociation voltage is only 0.7-2 V, and the first limiting current density is as low as 1-5 mA cm -2 .
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a bipolar membrane based on a charged nanosheet catalyst layer, comprising the following steps: A) applying a cation (anion) exchange membrane liquid on a smooth substrate and drying it to obtain a cation (anion) exchange membrane layer; dissolving the modified charged nanosheets to obtain a modified charged nanosheet solution; B) ultrasonically spraying the modified charged nanosheet solution on the cation (anion) exchange membrane layer, and drying to obtain a bipolar membrane intermediate layer; C) ultrasonically spraying anion (cation) exchange membrane liquid onto the middle layer of the bipolar membrane, and drying to obtain a bipolar membrane.
2. The preparation method according to claim 1, characterized in that: The surface modification groups of the modified positively (negatively) charged nanosheets are one or more of ions, ionic groups, colloidal molecules and polymer molecules with a size of 0.1 to 20 nm; The modified charged nanosheets are boron nitride nanosheets, MXene nanosheets, graphene family nanosheets, hydrotalcite nanosheets, disulfide nanosheets, zeolite nanosheets, MOF nanosheets or TiO2 nanosheets.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the cation (anion) exchange membrane liquid is 1 to 10%; The solvent in the cation (anion) exchange membrane liquid is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide.
4. The preparation method according to claim 1, characterized in that: The drying temperature in step A) is 50-90°C for 1-48 hours; the thickness of the cation (anion) exchange membrane layer is 1-40 μm; The drying temperature in step B) is 50-90°C; The drying temperature in step C) is 50-90° C. and the drying time is 1-48 hours; the thickness of the anion (cation) exchange membrane layer is 1-40 μm.
5. The preparation method according to claim 1, characterized in that: The solvent used for dissolving the modified charged nanosheets is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide; The mass volume ratio of the modified charged nanosheets and the solvent is (0.1-1) g: (200-1000) mL.
6. The preparation method according to claim 1, characterized in that: In step B), the thickness of the bipolar membrane intermediate layer is 4 to 400 nm; The loading amount of the modified charged nanosheets on the cation (anion) exchange membrane layer is 1 to 1000 μg / cm -2 .
7. The preparation method according to claim 1, characterized in that: The mass concentration of the anion (cation) exchange membrane liquid in step C) is 1 to 10%; The solvent in the anion (cation) exchange membrane liquid is selected from one or more of water, methanol, ethanol, N,N-dimethylformamide and dimethyl sulfoxide.
8. The preparation method according to claim 1, characterized in that: The spraying height in step B) and step C) is 1 to 10 cm; The solution spray rate was set at 0.05-0.8 mL min -1 , feed speed is 5~40mm·s -1 .
9. A bipolar membrane based on a charged nanosheet catalyst layer, prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a bipolar membrane prepared by the preparation method according to any one of claims 1 to 8 in seawater separation.
Citation Information
Patent Citations
MXene composite membrane, electrodialysis device, preparation method and application of MXene composite membrane
CN116272416A
Two-dimensional titanium-carbon-based bipolar membrane and preparation method thereof
CN116351255A
Preparation method of MXene bipolar membrane based on polycation gel modification
CN117180999A
MOF (Metal Organic Framework)-based / graphene oxide composite bipolar membrane as well as preparation method and application thereof
CN118743919A
Image Restoration Method and Imaging System for performing the same
KR102881274B1
Cited By
Aminated modified graphene oxide based bipolar membrane and preparation method thereof
CN122076258A
An aminated graphene oxide-based bipolar film and its preparation method
CN122076258B
Preparation method of bipolar membrane intermediate catalyst layer material
CN122076527A